2016
DOI: 10.1016/j.bbi.2016.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Clenbuterol activates the central IL-1 system via the β2-adrenoceptor without provoking inflammatory response related behaviours in rats

Abstract: The long-acting, highly lipophilic, β2-adrenoceptor agonist clenbuterol may represent a suitable therapeutic agent for the treatment of neuroinflammation as it drives an anti-inflammatory response within the CNS. However, clenbuterol is also known to increase the expression of IL-1β in the brain, a potent neuromodulator that plays a role in provoking sickness related symptoms including anxiety and depression-related behaviours. Here we demonstrate that, compared to the immunological stimulus lipopolysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 100 publications
(144 reference statements)
0
4
0
Order By: Relevance
“…An in vitro study showed that β2-AR activation dampened the LPS-induced M1 polarization in macrophages (Bacou et al, 2017). Another study confirmed that the peripheral effects of clenbuterol can be dissociated from its central effects and the increased expression of the antiinflammatory molecules IL-1ra and IL-1RII may serve to limit the effects of clenbuterol-induced IL-1β on brain function and behavior (Ryan et al, 2016). In the present study, we extended these prior studies in vivo by demonstrating that activation of the β2-adrenergic receptor not only regulated the production of inflammatory cytokines but also modified the entire microglia phenotype, resulting in an M2 regulatory microglia phenotype.…”
Section: Discussionmentioning
confidence: 84%
“…An in vitro study showed that β2-AR activation dampened the LPS-induced M1 polarization in macrophages (Bacou et al, 2017). Another study confirmed that the peripheral effects of clenbuterol can be dissociated from its central effects and the increased expression of the antiinflammatory molecules IL-1ra and IL-1RII may serve to limit the effects of clenbuterol-induced IL-1β on brain function and behavior (Ryan et al, 2016). In the present study, we extended these prior studies in vivo by demonstrating that activation of the β2-adrenergic receptor not only regulated the production of inflammatory cytokines but also modified the entire microglia phenotype, resulting in an M2 regulatory microglia phenotype.…”
Section: Discussionmentioning
confidence: 84%
“…It is unclear if the production of IL-1 β via β -AR signaling depends on activation of an inflammasome or if it is mediated by an inflammasome-independent pathway, as is observed with other sterile inflammatory stimuli [77–79]. Clenbuterol, a β 2 -AR agonist, administered to rats selectively induces IL-1 β and not IL-6 or TNF- α in the hypothalamus and hippocampus [80]. Figure 3 demonstrates similar responses in primary microglia incubated with various concentrations of norepinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…The sex differences may involve the magnitude by which glucocorticoids regulate norepinephrine release between males and females since metyrapone-treatment increased norepinephrine turnover in the hypothalamus and medial prefrontal cortex of male rats while having no effect on norepinephrine turnover in females In both males and females, propranolol blocked the increase in IL-1β mRNA induced by metyrapone-treatment indicating the increase in IL-1β expression was dependent on β-AR activation. Ryan et al (2016) demonstrated that β-ARs regulate IL-1β production in microglia. To examine if microglia were a potential cellular source of IL-1β mRNA in our studies, we used a Percoll gradient to isolate microglia (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Catecholamines can stimulate the production of IL-1β in microglia (Ryan et al, 2016), thus we hypothesized that microglia may be a cellular source of the increase in IL-1β following metyrapone. To test this, male Fischer rats (n=4/group) were given an injection of either saline or metyrapone and 2 h later animals were euthanized and microglia were isolated from the hypothalamus and hippocampus for the measurement of IL-1β mRNA.…”
Section: Experimental Designmentioning
confidence: 99%